Literature Review: The Influence of the Whistleblowing System on Fraud Prevention in Local Governments - Rahmi, Andi Faika; Akib, Mulyati; Intihanah, Intihanah (Dinasti Publisher, 2026)
This study aims to analyze the influence of the whistleblowing system on fraud prevention in the public sector, particularly in local governments. The literature review was conducted by examining various research findings from the past five years. The results indicate that the whistleblowing system has the potential to reduce fraud risks through secure and confidential reporting channels. However, its effectiveness is highly dependent on whistleblower protection, organizational culture, and robust internal controls. Some studies also found that the whistleblowing system does not always have a significant impact on fraud prevention if not supported by other critical factors. Therefore, optimal fraud prevention requires synergy between the whistleblowing system, internal controls, and an integrity-based organizational culture.